1996
DOI: 10.3354/meps143025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term distribution patterns of mobile estuarine invertebrates (Ctenophora, Cnidaria, Crustacea:Decapoda) in relation to hydrological parameters

Abstract: Between 1977 and 1992, semi-quantitative samples of macroinvertebrates were taken at fortnightly intervals from the Thames Estuary (UK) utilising the cooling water intake screens of West Thurrock power station. Samples were taken for 4 h over low water, the abundances of invertebrates recorded in 30 min subsamples and related to water volume filtered. Abundances of the major estuarine species have therefore been recorded every 2 wk for a 16 yr period, together wlth physicochemical parameters such as temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…From then until 1991 there were only sporadic sightings of this species (Ingle 1986). During 1991During -1992 there was a marked increase in their abundance at West Thurrock Power Station (Attrill and Thomas 1996a) and indications of a seaward migration of adults occurring in October and November of 1992. It was speculated that the reason for this sudden increase in the population was the decrease in freshwater flows following a drought period in the Thames in 1989-1991, which allowed the establishment of a young population (Attrill and Thomas 1996a).…”
Section: Introductionmentioning
confidence: 98%
“…From then until 1991 there were only sporadic sightings of this species (Ingle 1986). During 1991During -1992 there was a marked increase in their abundance at West Thurrock Power Station (Attrill and Thomas 1996a) and indications of a seaward migration of adults occurring in October and November of 1992. It was speculated that the reason for this sudden increase in the population was the decrease in freshwater flows following a drought period in the Thames in 1989-1991, which allowed the establishment of a young population (Attrill and Thomas 1996a).…”
Section: Introductionmentioning
confidence: 98%
“…It was first found in the San Francisco Estuary in 1992 and since that time has increased rapidly in abundance and range, as it did previously in the Thames Estuary (Attrill and Thomas 1996). In contrast to most crabs, the mitten crab is catadromous, rearing in rivers and sloughs upstream and reproducing in brackish water (Halat and Hieb 1996;Rudnick et al 2003).…”
Section: Introduced Crabsmentioning
confidence: 99%
“…On the other hand, the adult individuals that overwinter are found closer to the sediment and, hence, less obvious in plankton samples. Nevertheless, much is still unknown concerning the population dynamics of Pleurobrachia, and other authors have observed other overwintering strategies for different Pleurobrachia species and different localities (Milne and Corey 1986;Attrill and Thomas 1996). When the population builds up through intense reproduction in spring, the average size of the individuals decreases, to reach a minimum around August (Greve 1971), and main reproduction is early in the season.…”
Section: Introductionmentioning
confidence: 99%